Ergodic theory and its connection with harmonic analysis proceedings of the 1993 Alexandria conference - Petersen, Karl Endel 1943-; Salama, Ibrahim A. (Cambridge University Press, 1995)
Ergodic theory is a field that is stimulating on its own, and also in its interactions with other branches of mathematics and science. In recent years, the interchanges with harmonic analysis have been especially noticeable and productive. This book contains survey papers describing the relationship of ergodic theory with convergence, rigidity theory and the theory of joinings. These papers present the background of each area of interaction, the most outstanding results and promising lines of research. They should form perfect starting points for anyone beginning research in one of these areas. Thirteen related research papers describe the work; several treat questions arising from the Furstenberg multiple recurrence theory, while the remainder deal with convergence and a variety of other topics in dynamics
Title from publisher's bibliographic system (viewed on 05 Oct 2015)
Keywords: Ergodic theory / Congresses; Harmonic analysis / Congresses; Harmonische Analyse; Ergodentheorie; Konferenzschrift